The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-018-36239-w
|View full text |Cite
|
Sign up to set email alerts
|

The biogenic amines putrescine and cadaverine show in vitro cytotoxicity at concentrations that can be found in foods

Abstract: Putrescine and cadaverine are among the most common biogenic amines (BA) in foods, but it is advisable that their accumulation be avoided. Present knowledge about their toxicity is, however, limited; further research is needed if qualitative and quantitative risk assessments for foods are to be conducted. The present work describes a real-time analysis of the cytotoxicity of putrescine and cadaverine on intestinal cell cultures. Both BA were cytotoxic at concentrations found in BA-rich foods, although the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 31 publications
3
84
0
1
Order By: Relevance
“…In this regard, we performed a Pearson correlation analysis with ruminal concentrations of biogenic amines and LPS (Humer et al, 2018). Biogenic amines are naturally occurring nitrogenous compounds synthesized by plants, animals and microorganisms, mainly through the decarboxylation of amino acids; however, ingestion can provoke serious toxicological reactions (Del Rio et al, 2019). In the current study, the highest correlation to biogenic amines was found between Anaerovibrio and the biogenic amines cadaverine and tyramine.…”
Section: Role Of Phymentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we performed a Pearson correlation analysis with ruminal concentrations of biogenic amines and LPS (Humer et al, 2018). Biogenic amines are naturally occurring nitrogenous compounds synthesized by plants, animals and microorganisms, mainly through the decarboxylation of amino acids; however, ingestion can provoke serious toxicological reactions (Del Rio et al, 2019). In the current study, the highest correlation to biogenic amines was found between Anaerovibrio and the biogenic amines cadaverine and tyramine.…”
Section: Role Of Phymentioning
confidence: 99%
“…Since changes in biogenic amines can be seen under low pH conditions (Humer et al, 2018), without large increases in pathogenic bacteria (Neubauer et al, 2018), it can be speculated that a change in the metabolism of rumen epithelial microbiota, not the alteration in relative abundances of pathogenic microbiota, are the underlying cause for the production of biogenic amines and endotoxins. The mode of cytotoxic action putrescine and cadaverine is the initiation of cell necrosis (Del Rio et al, 2019). Histamine, a highly pro-inflammatory amine, has been previously speculated as the causative agent in rumen epithelial inflammation and during SARA due to its role in laminitis (Nocek, 1997).…”
Section: Role Of Phymentioning
confidence: 99%
“…In the current study, the changes in the microbial composition could consistently explain the significant reduction in the levels of biogenic amines (histamine, putrescine, and tyramine) in the coriander soy sauce samples. The presence of histamine, putrescine, and tyramine, as well as other biogenic amines in food, is associated with health risks; owing to their potential toxicity, avoiding their accumulation in foods is advisable [ 36 ]. Histamine poisoning is a known risk factor associated with the consumption of histamine-rich foods and could lead to serious allergen-type reactions at high levels [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike HIS and TYR, the pharmacological activities of PUT and CAD seem to be less potent. Nonetheless, both amines show in vitro cytotoxicity at concentrations easily reached in inherently BA-rich foods [77] and enhance the toxicity of HIS and TYR [19]. In the tested teuktrey (fish sauce) products, the highest levels of PUT (404 ppm) and CAD (766 ppm) were higher than those in fish sauce sold at Malaysian markets (242.8 ppm PUT and 704.7 ppm CAD) [78] and Chinese markets (276.6 ppm PUT and 606.3 ppm CAD) [73] but much lower than the levels in imported fish sauce products sold at German markets (1257 ppm PUT and 1429 ppm CAD) [75], Austrian markets (510 ppm PUT and 1540 ppm CAD) [65], and other European markets (1220 ppm PUT and 1150 ppm CAD) [60].…”
Section: Bas and Food Safetymentioning
confidence: 99%
“…Furthermore, PUT and CAD increase with longer storage times [19] and give strong unpleasant decaying odors at very low concentrations [75]. Therefore, the PUT and CAD concentration could be used as quality indicator [19], and their accumulation should be avoided [15,77]. These BAs are also included in the biogenic amine index (BAI) [83].…”
Section: Bas and Food Qualitymentioning
confidence: 99%